Ciclo vigília-sono em adolescentes do ensino médio: caracterização, impacto da asma e de um programa de educação sobre sono - Ferreira, Luana Gabrielle de França (2022)
The present thesis comprises three studies. The first evaluated adolescents’ sleep pattern, sleep quality, and daytime sleepiness, and examined the association of sex, chronotype, and social jetlag with their sleep quality. The second study investigated the impact of social jetlag on the degree of asthma control and the relationship between asthma and sleep quality, excessive daytime sleepiness, characteristics of the sleep-wake rhythm, and chronotype in adolescents. The third study evaluated the effects of intervention through a health education program on sleep on adolescents' sleep knowledge, habits, pattern, and quality. The research was developed in two stages: the first comprised a cross-sectional design with adolescent students in full-time high schools and the morning shift of ten schools, resulting in two studies. In the second stage, a longitudinal and intervention design was used to evaluate the effects of a sleep education program (PESS) on the sleep-wake cycle. Sociodemographic variables, chronotype, sleep schedule on school days and free days, social jetlag, sleep quality, excessive sleepiness score, asthma score, and asthma control score were collected. One thousand four hundred fifty-seven adolescents participated in the study, with a mean age of 16.1 ± 1.1 years; 53.9% were female, and 61.8% were in full-time education. In the first study, it was observed that 87.8% had low sleep duration (< 8h) on school days; 60.1% and 42% had poor sleep quality and excessive daytime sleepiness, respectively, and 76.2% reported daytime naps. In the logistic regression analysis, poor sleep quality was more significant in females; individuals with low sleep duration, afternoon chronotype, social jetlag (> 3.7h), daytime sleepiness and those who studied the entire shift. In the second study, 250 (17.2%) had a medical diagnosis and/or symptoms compatible with asthma, who were classified into groups: uncontrolled and controlled. It was observed that uncontrolled and controlled asthma groups had a higher percentage of poor quality sleep (81.7% vs. 77.4% vs. 56.5%, respectively) and a greater frequency of excessive daytime sleepiness (56.2% vs. 56.5% vs. 39.2%, respectively). There was no significant relationship between social jetlag and the presence and degree of asthma control. In the third study, 163 adolescents with a mean age of 16.6 ± 0.7 years participated in the study, the PESS intervention group, an increase in the number of correct answers was observed in 41.2% of the questions about sleep knowledge; however, there was no significant increase in sleep duration. On free days, there was a reduction in sleep onset and, consequently, a decrease in social jetlag in the intervention group. In conclusion, high school adolescents have insufficient and poor quality sleep and excessive daytime sleepiness, with frequent daytime naps. Students with asthma, regardless of the degree of control, have more excessive daytime sleepiness and insufficient and poor quality sleep than adolescents without asthma. The intervention program in the proposed molds allowed the acquisition of knowledge about sleep-related aspects but was not sufficient for substantial behavioral change. These results have implications for interventions focused on sleep quality in adolescents.